The Effect of Natural Buffer on Biohydrogen Production - Choiron, Miftahul; Tojo, Seishu; Chosa, Tadashi (Institute of Research and Community Outreach - Petra Christian University, 2021)
Hydrogen is the promising ideal energy carrier with no emission but water on its combustible in the next generation. Hydrogen production using biological methods is greener than other methods using fossil fuel. One of the major factors affecting the operation of biohydrogen production is pH level in bioreactors. Restrain of declining pH is expected to increase hydrogen production. Pretreatment is one key factor in successful biohydrogen fermentation using mixed microbes. This study aims to investigate the natural buffer effect on biohydrogen using hot compressed water pretreatment. This batch fermentation experiment was operated in a 110 mL glass reactor with 3.75 g/L glucose as substrate. Mixed culture was obtained from cow dung compost treated with hot compressed water pretreatment at 150 ºC, 0.5 MPa for 40 minutes. Fine dried eggshell powder and calcinated eggshell were added with 1 g/L, 3 g/L, and 5 g/L concentrations as buffer agents. The result showed that the addition of 1 g/L eggshell obtained the highest hydrogen production rate of 0.92 mol H2/mol glucose. Butyric acid and acetic acid are recognized as an indicator of hydrogen production and the Butyric/Acetic molar ratio over 2.6 as efficient biohydrogen fermentation. The highest B/A ratio in this experiment was 4.62 on 3g/L addition of eggshell powder.